STUDI EKSPERIMEN FINISHING PERHIASAN KUNINGAN DENGAN PERPADUAN ELEKTROPLATING DAN PATINASI - Febrian Wisnu Adi (Corak : Jurnal Seni Kriya, 2018)
Finishing Research The combination of Patina and electroplating has been carried out according to the research target, which has been able to identify metal materials, especially brass and copper. Bronze and copper Patenting techniques with various jewelry forms. The form of jewelry created amongst other things: bracelets, pendants, jewelry earrings are made with solder technique, tatah, and saws. Before the author experiment and apply patina and electroplating as the main finishing on jewelry on the work of creation. The author first conducted patina and electroplating tests to brass and copper plates with size 2 x 3 cm. The process and results of this research experiment is the answer and the first step which has successfully conducted various scientific experiments with found patina finishing formula with the ideal chemical mixing composition. Research on patina and electroplating experiments can be a contribution to the progress of finishing. Patina finishing research is preferred in brass and copper.Finishing is the finishing touch of a product with a better purpose, such as increasing the quality of the ingredients, increasing the decorative value, increasing the aesthetic value of a product, following the latest design trends, and can increase the selling value of a product. This research is a new research that has not been there before with the method of merging patina and electroplating techniques will be a trend finishing and as a pioneer finishing on jewelry with brass and copper. Keywords: jewelry finishing experiment, patination finishing, finishing electroplating  Percobaah finishing kombinasi patina dan electroplating telah dilakukan sesuai dengan target penelitian, yang telah mampu mengidentifikasi bahan logam, khususnya kuningan dan tembaga. Teknik Paten Perunggu dan Tembaga dengan berbagai bentuk perhiasan. Bentuk perhiasan yang dibuat antara lain: gelang, liontin, anting perhiasan dibuat dengan teknik solder, tatah, dan gergaji. Sebelum penulis bereksperimen dan menerapkan patina dan pelapisan sebagai finishing utama pada perhiasan pada karya penciptaan. Penulis pertama kali melakukan tes patina dan elektroplating untuk pelat kuningan dan tembaga dengan ukuran 2 x 3 cm. Proses dan hasil percobaan penelitian ini adalah jawaban dan langkah pertama yang berhasil melakukan berbagai percobaan ilmiah dengan menemukan formula finishing patina dengan komposisi pencampuran kimia yang ideal. Penelitian tentang percobaan patina dan elektroplating dapat menjadi kontribusi bagi kemajuan penyelesaian. Penelitian finishing Patina lebih disukai di kuningan dan tembaga. Finishing adalah sentuhan akhir dari produk dengan tujuan yang lebih baik, seperti meningkatkan kualitas bahan, meningkatkan nilai dekoratif, meningkatkan nilai estetika suatu produk, mengikuti tren desain terbaru, dan dapat meningkatkan nilai jual suatu produk. Penelitian ini adalah penelitian baru yang belum pernah ada sebelumnya dengan metode penggabungan patina dan teknik elektroplating akan menjadi tren finishing dan sebagai pelopor finishing pada perhiasan dengan kuningan dan tembaga. Kata kunci: percobaan finishing perhiasan, finishing patinasi, finishing electroplating